A new geometrical inverse kinematics method for planar hyper redundant manipulators - Yahya, S.; Mohamed, H.A.F.; Moghavvemi, M.; Yang, S.S. (2009)
Obtaining the joint variables that result in a desired position of the robot end-effector called as inverse kinematics is one of the most important problems in robot kinematics and control. As the complexity of robot increases, obtaining the inverse kinematics solution requires the solution of non linear equations having transcendental functions are difficult and computationally expensive. This paper proposed a new geometrical method to find the inverse kinematics of the planar redundant manipulators. Using the proposed method, singularity avoidance is achieved by setting the angles between the adjacent links to be equal, which makes it impossible for any two or more joint axes to line up. Two study cases are simulated in this paper to show the performance of the proposed method.